2016
DOI: 10.1111/dmcn.13159
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous immunoglobulin in paediatric neurology: safety, adherence to guidelines, and long‐term outcome

Abstract: Our study demonstrates that IVIG is generally well tolerated but expensive, and discloses discrepancies between guidelines and clinical practice in paediatric neurology, suggesting both the need for greater adherence to current recommendations, and for recommendations to be updated to accommodate emerging indications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
44
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(46 citation statements)
references
References 43 publications
0
44
0
2
Order By: Relevance
“…It was well suggested that the clinical therapy of hIVIg is generally of preferable tolerance in patients, with common adverse effects like headache, fever, vomiting, or local skin problems at the site of cannula insertion in 25.5% of the total cohort (177). While for the choice of plasma exchange, unique challenges in patients should be taken into consideration such as patients’ poor cooperativity or autonomic instability, and other complications, especially in the crowd of children.…”
Section: Discussionmentioning
confidence: 99%
“…It was well suggested that the clinical therapy of hIVIg is generally of preferable tolerance in patients, with common adverse effects like headache, fever, vomiting, or local skin problems at the site of cannula insertion in 25.5% of the total cohort (177). While for the choice of plasma exchange, unique challenges in patients should be taken into consideration such as patients’ poor cooperativity or autonomic instability, and other complications, especially in the crowd of children.…”
Section: Discussionmentioning
confidence: 99%
“…La dosis dependerá de cada trastorno (Cuadro 5). (GRADE C2) 197,198,199,200 Infecciones Citomegalovirus El tratamiento de elección para primoinfección por citomegalovirus (CMV) en pacientes con trasplante de órganos sólidos (TOS) o trasplante de células hematopoyéticas consiste en antivirales específicos como ganciclovir intravenoso o valganciclovir oral. Los medicamentos alternos ante resistencia son cidofovir y foscarnet.…”
Section: Encefalitis De Rasmussenunclassified
“…Amalou et al 2 report 10 patients with GLUT1-DS treated with MAD for 2.5 years. The outcomes they observed are similar, even in infants, to reports of treatment with the classical ketogenic diet.…”
Section: Supporting Informationmentioning
confidence: 99%
“…The MAD and classical ketogenic diet were used respectively in 17 (55%) and 11 patients (35%). 1 Amalou et al 2 reported a mean age at diagnosis of 6.2 years (standard deviation [SD] 1.7), whereas the first signs were noted at the age of 1.5 years (SD 0.4). Low ketone concentrations (e.g.…”
Section: Supporting Informationmentioning
confidence: 99%
See 1 more Smart Citation